Stereotactic Ablative Radiation Therapy for Metastatic Renal Cell Carcinoma – A Review of Evidence - Bora, Hima; Sarma, Gautam; Medhi, Partha Pratim (Acta medica Lituanica, 2025)
Because of its remarkable precision in providing targeted radiation, recent evidence supports Stereotactic Ablative Radiation Therapy (SABR) as a promising non-invasive treatment approach for metastatic renal cell carcinoma, minimizing harm to adjacent healthy tissues. With regards to its heterogeneous nature with diverse clinical presentations, rapid progression and metastatic potential, Renal Cell Carcinoma (RCC) is known to make therapy more challenging, and also to reduce the survival rates. Even though Immune Checkpoint Inhibitors (ICIs) remain the gold standard for treating metastatic RCC (mRCC), certain patients with one or a few distant metastases seem to have a longer survival period if the metastases are surgically removed. However, complete responses are not always the case, with radiation being increasingly incorporated as a component of multidisciplinary care. Moreover, studies proving the immunogenic qualities of hypofractionated SABR and the safety and potential of combining SABR with immune-based and surgical therapy for mRCC are becoming more prevalent in the literature. SABR helps induce local inflammation with the tumour, promoting T cell activation and antigen presentation. Multiple retrospective and prospective reports have also demonstrated that SABR assigned to the metastatic locations of mRCC, while using ablative dosages, achieves high local control rates with a good toxicity profile, thus disproving earlier theories of RCC radioresistance. This review outlines the key evidence favouring SABR being administered to metastatic tumours, including the results of recent prospective phase 2 trials in patients with oligometastatic, oligoprogressive, and unselected mRCC. The body of data that has been gathered points to SABR as a promising indicator that is being utilized more and more in the multidisciplinary management of mRCC.
Keywords: stereotactic ablative radiation therapy; metastatic renal cell carcinoma; oligometastatic renal cell carcinoma; oligoprogressive renal cell carcinoma; renal cell carcinoma